The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1159/000498861
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity in Asthma, Allergic Conditions and COPD Increase Disease Severity, Drug Use and Costs: The Finnish Pharmacy Survey

Abstract: Background: Asthma, allergic conditions, and COPD overlap, but the effect of them and their combinations on disease severity, need for drugs, use of healthcare, and costs is poorly known. Objective: To study how different allergic diseases co-occur in asthma and allergy patients and evaluate the use of medication well as drug and healthcare costs. Methods: Nationwide Allergy Barometer Survey was carried out in the Finnish pharmacies during 1 week in September 2016. Altogether, 956 patients (5–75 years) who pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
0
24
1
Order By: Relevance
“…In addition, data from the mobile application MASK-air have identified an extreme pattern of uncontrolled multimorbidity (uncontrolled rhinitis, conjunctivitis and asthma during the same day) 32 . More recent classical epidemiological studies showed that ocular symptoms are more common in polysensitized patients 29 whether they have asthma or do not have asthma 30 , ocular symptoms are associated with the severity of nasal symptoms 33 , ocular symptoms are important to consider in severe asthma 33 and the severity of allergic diseases increases with the number of allergic multimorbidities 34 .…”
Section: Multimorbidities and Sensitizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, data from the mobile application MASK-air have identified an extreme pattern of uncontrolled multimorbidity (uncontrolled rhinitis, conjunctivitis and asthma during the same day) 32 . More recent classical epidemiological studies showed that ocular symptoms are more common in polysensitized patients 29 whether they have asthma or do not have asthma 30 , ocular symptoms are associated with the severity of nasal symptoms 33 , ocular symptoms are important to consider in severe asthma 33 and the severity of allergic diseases increases with the number of allergic multimorbidities 34 .…”
Section: Multimorbidities and Sensitizationmentioning
confidence: 99%
“…In this regard, differences between AR alone and AR associated with conjunctivitis were previously known 29 but epidemiological studies using data from mobile applications demonstrated that ocular symptoms are more common in patients with polysensitization 30 , are associated with nasal symptom severity 33 and are important to consider in severe asthma 33 . Moreover, the severity of allergic diseases increases with the number of allergic multimorbidities 34 . This is the first example of a discovery of novel allergic phenotypes using a mobile health application confirmed by classic epidemiological studies.…”
Section: Mobile Healthmentioning
confidence: 99%
“…Many people with asthma also have other comorbidities such as rhinitis and eczema. 1 In previous studies, having more than one allergic disease has been linked to poorer asthma control, a poorer prognosis, breathing-related comorbidities, such as sleep apnoea, 2 and poorer quality of life. 3,4 It is known that allergic sensitization increases the risk of asthma, rhinitis and eczema, 5 but multimorbidity with asthma, rhinitis and eczema can occur both with and without the presence of atopy.…”
Section: Introductionmentioning
confidence: 99%
“…CDSSs may also be very useful in stratification strategies and in reporting outcomes in clinical trials such as in Allergen Immunotherapy (https://www.ncbi.nlm.nih.gov/pubmed/30955224). (iv) the severity of allergic diseases increases with the number of allergic multimorbidities (75). This is the first time that novel allergic phenotypes have been discovered using an mHealth app and then confirmed by classical epidemiologic studies.…”
Section: -Clinical Decision Support Systems (Cdsss)mentioning
confidence: 76%